PENGARUH GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP LOYALITAS KARYAWAN (STUDI KASUS HOTEL OLGARIA PEKANBARU) - ", Marfuah; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study was to determine the effect of democratic leadership style to theloyalty of employees (Case Study Olgaria Hotel Pekanbaru). The study population ofall employees in the hotel Olgaria Pekanbaru totaling 35 people. Analysis of the datain this study using SPSS. Sampling techniques using the census method and dataanalysis techniques used in this study include validity, reliability, simple linearregression and t-test to test and prove the research hypothesis.The analysis showed that the influence of the democratic leadership style tothe loyalty of employees . Based on the results obtained by the value of r (correlationcoefficient) amounted to 54.3% 0543% means that the democratic leadership stylevariable significant effect on employee loyalty Olgaria Hotel Pekanbaru. Results ofhypothesis testing found that t-count larger than t-table which means Ha accepted.Keywords: democratic leadership style and employee loyalty